8 Analisis Kinerja Pegawai Sekolah Tinggi Teknologi Kedirgantaraan Yogyakarta Tahun 2017 - Elnia Frisnawati (Jurnal Manajemen Dirgantara, 2019)
This study aims to determine the search for factors that influence the performance of employees at the Aerospace Technology College. This study uses Multiple Linear Regression analysis tools, the subjects of this study are STTKD employees. Factors that influence employee performance which is one of the important factors in improving company performance making it easier for companies to focus on factors that significantly influence the performance of STTKD employees. The results of this study prove that the factors of motivation, leadership, compensation and organizational climate have a significant influence on employee performance